Candlenut Milk and Cream Application for Non-Dairy Ice Cream with Higher Polyunsaturated Fatty Acid - Wijaya, Hamdarian; Fortunata, Stacia Andani; Rahmawati, Della (Journal Akademik Universitas Swiss German, 2021)
Lower ability to digest lactose limits the consumption of dairy products for children and teenagers. Candlenut is a known source of polyunsaturated fatty acid that can be processed into candlenut milk and cream as an alternative ingredient in the production of non-dairy food products, such as candlenut ice cream. However, the application of candlenut to the food products requires some optimizations. This research aimed to explore the optimized formula and overcome the limitations in nutritional requirement, sensory acceptance, and saponin content. Compared to dairy products, the utilization of candlenut will result in undesirable texture due to its unsaturated fatty acid content. The addition of stabilizer was able to improve the texture and was comparable to the dairy ice cream. The formulation was optimized by Design Expert software, resulted in selected formula using 49.7% candlenut cream, 29.8% of candlenut milk, 19.9% of sugar, and 0.55% stabilizer which had score 7.07±1.3 (“like moderately”) of the overall acceptance by hedonic test. The iodine value of the candlenut ice cream was higher (21.56 ± 0.60) compared to dairy ice cream (4.89 ± 0.13). The selected formula of candlenut ice cream also passed the Indonesian National Standard (SNI) in fat, sugar, protein content, total soluble solid and total plate count spoilage aspects. The saponin content (49.34 ± 0.23) was also in the range of daily intake limit.